The effects of periodontal therapy on serum and salivary leptin levels in chronic periodontitis patients with normal body mass index. (November 2015) - Purwar, Parth; Khan, Mohammed Akhlaq; Gupta, Abhishek; Mahdi, Abbas Ali; Pandey, Shivani; Singh, Babita; Dixit, Jaya; Rai, Priya
Abstract: Summary. Leptin concentrations are altered in favour of pro health after periodontal therapy. Background. Leptin, a non-glycosylated peptide hormone, not only maintains fat stores, but is also an integral part of host defense repertoire. Leptin levels have been found to be altered in an array of inflammatory diseases including chronic periodontitis (CP), but the role of non-surgical periodontal therapy (NSPT) in altering the leptin concentrations in saliva and serum of CP patients is yet to be ascertained. The aim of the present study is to quantify leptin levels in CP patients having normal body mass index (BMI) pre-therapy as compared to periodontally healthy controls and to address whether successful NSPT alters leptin concentration in serum and saliva. Materials and methods. Twenty-two saliva (modified draining method) and serum samples (by venipuncture) were collected from CP patients with normal BMI ( n = 22), before and at 4 and 12 weeks after completion of NSPT, and periodontally healthy, age- and gender-matched controls ( n = 22). Leptin levels were estimated using enzyme linked immunosorbent assay kits. Results. At baseline, CP patients had significantly different periodontal clinical parameters and the leptin concentrations in saliva of CP patients were found to be significantly lower than periodontally healthy volunteers (4710.10 ± 1133.21 vs 8721.10 ± 1019.58 pg/ml) ( p < 0.05), whereas in serum the leptin concentrations were significantly higher than healthy controls (10749 ± 2062.24 vs 8085.00 ± 2859.68 pg/ml). Significant improvement in periodontal parameters, serum and salivary leptin levels were observed in CP patients at 4 and 12 weeks post-therapy ( p < 0.01). Conclusion. Altered concentrations of leptin in serum and saliva are observed in CP patients which can be restored in favor of health after periodontal therapy.